Hubungan Pengetahuan Mengenai Kanker Payudara Dalam Mengelola Kecemasan Dan Pengobatan Komplementer - Adyani, Asta (Universitas Muhammadiyah Surabaya, 2024)
Objective: The large number of breast cancer sufferers and the lack of knowledge have resulted in many sufferers experiencing excessive anxiety; this is one of the factors for the government to focus more on providing education to the public. Methods: This research design uses a systematic review of data sources obtained from several articles collected by conducting computer searches via Google Scholar of the articles that have been searched. Population and sample from research article entitled Relationship between knowledge about breast cancer and awareness behavior (breast self-examination), description of anxiety and depression in women with breast cancer, Indonesian Journal of Community Empowerment (IJCE) The importance of breast self-examination (SADARI) as an early detection effort Breast cancer, experience of using complementary therapy in breast cancer patients, comparative analysis of the CART algorithm classification with C 4.5 in cases of breast cancer sufferers. Results: The article discusses primarily breast cancer and knowledge about breast cancer so that you can manage anxiety. Early detection of breast cancer can be done using a BSE examination. This examination can easily detect signs of breast cancer. Conclusion: Breast cancer is a deadly cancer and affects many women in Indonesia and even around the world. The BSE examination is an early detection that is easy to carry out, and anxiety in breast cancer sufferers is normal. Patients who are afraid of undergoing surgery prefer complementary therapy, but this therapy takes longer to heal.